Molecular Analysis and Activities of Bioactive Compounds from Symbiont Bacteria Isolates Polycarpa aurata - Herwin Herwin; Gemini Alam; Sartini Sartini; Abdul Rahim; Ayyub Harly Nurung; Amirullah Amirullah; Nasrul Haq (Majalah Obat Tradisional, 2026)
Symbiont bacteria associated with Polycarpa aurata are known to produce secondary metabolites with diverse bioactive properties, including antibacterial, anticancer, antifungal, and antiprotozoal activities. This study evaluated the antibacterial and antibiofilm activities of symbiotic bacterial isolates obtained from the white morphotype of P. aurata collected from Barrang Lompo Island, Makassar City, Indonesia. The agar diffusion method and ELISA reader assay were employed for antibacterial and antibiofilm analyses, respectively. Four pure isolates were obtained and designated AQ2-1, AL2-3, AL2-4, and AL2-5. Molecular identification based on 16S rRNA gene sequencing indicated that isolate AQ2-1 corresponded to Pseudomonas aeruginosa strain AB18. This isolate exhibited a pronounced inhibition zone against Bacillus subtilis, with an optimal incubation period of 68 h for secondary metabolite production. Chemical analysis of the bioactive compounds from isolate AQ2-1 identified adenine riboside and bis(2-ethylhexyl) benzene-1,2-dicarboxylate as the major constituents. Adenine riboside exhibited the highest antibacterial activity, producing an inhibition zone of 12.2 mm against Escherichia coli ATCC 25922, while bis(2-ethylhexyl) benzene-1,2-dicarboxylate produced an inhibition zone of 10.8 mm against Staphylococcus epidermidis ATCC 14990. In the antibiofilm assay, adenine riboside achieved the highest inhibition at 77.09% against Staphylococcus aureus ATCC 25923, whereas bis(2-ethylhexyl) benzene-1,2-dicarboxylate inhibited Streptococcus mutans ATCC 25175 by 73.61%. These findings demonstrate that secondary metabolites produced by the AQ2-1 isolate of symbiont bacteria from P. aurata possess strong antibacterial and antibiofilm activities and may serve as promising candidates for future antimicrobial development.